PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP SEMANGAT KERJA KARYAWAN PADA PT.BANK TABUNGAN NEGARA, TBK - Sicillia Emma Sumampouw; Sontje Manuel Sumayku (JURNAL ADMINISTRASI BISNIS, 2016)
Abstract - This study was conducted to determine the effect of compensation and motivation on working spirit at PT.Bank Tabungan Negara. The population in this study as many as 66 employees and is used as a sample or respondents as many as 40 employees in PT.Bank Tabungan Negara. The results of calculations based on correlation analysis and multiple linear regreasi that compensation and motivation positive and significant impact on working spirit. Between these two variables, the motivation to have a more dominant effect on working spirit than compensation.Keywords: Compensation, motivation, working spirit